Correction: Identification of a serum-induced transcriptional signature associated with metastatic cervical cancer. - Anna Palatnik; Shuyun Ye; Christina Kendziorski; Marissa Iden; Jessica S Zigman; Martin J Hessner; Janet S Rader (PLoS ONE, 2018)
[This corrects the article DOI: 10.1371/journal.pone.0181242.].